Mahatma Jotiba Phule: An Educational Philosopher - Marwaha, Navjoti (THE PRIMARY TEACHER, 2010)
Experiments of great thinkers and educationists can act as beacon light to guide our thoughts. One such thinker, teacher, educationist and social revolutionist we had in India is Mahatma Jotiba Phule. He lived and worked in Maharashtra. The purpose of this article is to look into his thoughts and ideas as an answer to the present challenges of education and inequality in India. His thoughts and ideas were revolutionary. His single aim was universalisation of primary education. Mahatma Jotiba Phule concentrated on need of primary education, the essential qualities of primary teacher and the curriculum of primary education. He gave importance to upliftment of lower castes and women education and took necessary steps for this at that time. His wife had got pride of being the first lady teacher